PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBASIS GAME INTERAKTIF WORDWALL PADA PELAJARAN BAHASA INDONESIA KELAS VIII SMPN 2 SELONG - Ramadhani, Ilham; Hary Murcahyanto; Rohayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve the quality of the Indonesian language learning process for eighth-grade students at SMPN 2 Selong by implementing the Problem-Based Learning (PBL) model in conjunction with the interactive game platform Wordwall. The study employed a participatory Classroom Action Research (CAR) approach involving 43 students. Data were collected through observation, questionnaires, and documentation, and subsequently analyzed qualitatively through the stages of data condensation, presentation, and conclusion verification. The results indicate that the implementation of Wordwall-based PBL enhanced the quality of the learning process, evidenced by increased student engagement, collaboration skills, and active participation in learning activities. Questionnaire results revealed that all students responded positively to the instruction, with 53.49% identifying the interactive games as the most helpful activity for understanding the material. The integration of PBL and Wordwall rendered the learning experience more interactive, collaborative, student-centered, and meaningful. These findings suggest that the model holds potential as an alternative approach to improving the quality of Indonesian language instruction, although further extensive research is warranted.